'Prison facilities were not built with a woman in mind': an exploratory multi-stakeholder study on women's situation in Malawi prisons. Issue 3 (27th April 2020) - Gadama, Luis; Thakwalakwa, Chrissie; Mula, Chimwemwe; Mhango, Victor; Banda, Chikosa; Kewley, Stephanie; Hillis, Alyson; Van Hout, Marie-Claire
Abstract : Purpose: Sub-Saharan African prisons have seen a substantial increase in women prisoners, including those incarcerated with children. There is very little strategic literature available on the health situation and needs of women prisoners and their circumstantial children in Malawi. The study aims to explore this issue. Design/methodology/approach: A qualitative exploratory study using in-depth key informant interviews with senior correctional stakeholders (commissioner of prison farms, senior correctional management staff, senior health officials and senior officers in charge) ( n = 5) and focus group discussions (FGD) with women in prison of age between 18 and 45 years ( n = 23) and two FGD with correctional staff ( n = 21) was conducted in two prisons in Malawi, Chichiri and Zomba. Narratives were transcribed and analysed using thematic analysis. Findings: Three key themes emerged and are as follows: "hygiene and sanitary situation across multiple prison levels and subsequent health implications for women"; "nutritional provision and diets of women and children in prison"; and "women's access to prison-based and external health services". Divergence or agreement across perspectives around sanitation and disease prevention, adequacy of nutrition for pregnant or breast-feeding women, health status and access to prison-based health care are presented. Practical implications: Garnering a contemporary understanding of women's situation and their health-care needs in Malawian prisons can inform policy and correctional health practice change, the adaptation of technical guidance and improve standards for women and their children incarcerated in Malawi. Originality/value: There is a strong need for continued research to garner insight into the experiences of women prisoners and their children, with a particular emphasis on health situation.